Safety and Efficacy of Fecal Microbiota Transplantation for Grade IV Steroid Refractory GI-GvHD Patients: Interim Results From FMT2017002 Trial - Zhao, Ye; Li, Xuewei; Zhou, Yujing; Gao, Jin; Jiao, Yang; Zhu, Baoli; Wu, Depei; Qi, Xiaofei (Frontiers in Immunology, 2021)
Gastrointestinal (GI) tract graft-versus-host disease (GvHD) is a major cause of post-allo-HSCT (hematopoietic stem cell transplantation) morbidity and mortality. Patients with steroid-refractory GI-GvHD have a poor prognosis and limited therapeutic options. FMT2017002 trial (#NCT03148743) was a non-randomized, open-label, phase I/II clinical study of FMT for treating patients with grade IV steroid-refractory GI-GvHD. A total of 55 patients with steroid-refractory GI-GvHD were enrolled in this study. Forty-one patients with grade IV steroid-refractory GI-GvHD were included in the final statistical analysis. Of them, 23 patients and 18 patients were assigned to the FMT group and the control group, respectively. On days 14 and 21 after FMT, clinical remission was significantly greater in the FMT group than in the control group. Within a follow-up period of 90 days, the FMT group showed a better overall survival (OS). At the end of the study, the median survival time was >539 days in the FMT group and 107 days in the control group (HR=3.51; 95% CI, 1.21–10.17; p=0.021). Both the event-free survival time (EFS) (HR=2.3, 95% CI, 0.99–5.4; p=0.08) and OS (HR=4.4, 95% CI, 1.5–13.04; p=0.008) were higher in the FMT group during the follow-up period. Overall, the mortality rate was lower in the FMT group (HR=3.97; 95% CI, 1.34–11.75; p=0.013). No differences in the occurrence of any other side effects were observed. Our data suggest that the diversity of the intestinal microbiota could be affected by allo-HSCT. Although its effectiveness and safety need further evaluation, FMT may serve as a therapeutic option for grade IV steroid-refractory GI-GvHD. Clinical Trial Registration [ClinicalTrials.gov], identifier [NCT03148743].